Role of Culture Free Rapid ImmunoAssay (ELISA) and Genexpert (MTB/RIF) Technology in the Diagnosis of Tuberculosis - Shahida Hussain; Sikander Sultan; Saba Riaz; Hajra Hussain; Chetan lal (Proceedings, 2024)
Introduction: Prolonged laboratory processes are major hurdles in the early diagnosis of tuberculosis. Prompt management of this disease is utmost necessary to control its spread. For this purpose, use of rapid and reliable laboratory testing methods for the diagnosis of Mycobacterium tuberculosis are crucial alongwith timely infection management and preventing its transmission to the close contact population.